Applying a Training Needs Assessment through the Design Thinking methodology: an experience from the Centro de Capacitación en Educación a Distancia at the Universidad Estatal a Distancia (Revista Electrónica Calidad en la Educación Superior, 2025)
This article systematizes the experience of the training needs assessment carried out by the Centro de Capacitación en Educación a Distancia (CECED) during 2021-2022 at the Universidad Estatal a Distancia (UNED) in Costa Rica. The experience focused on designing and implementing a reflective assessment grounded in the human-centered methodology known as Design Thinking. Based on a document review, the methodological process was reconstructed, the results obtained were analyzed, and key lessons were identified. The methodology proved effective in fostering a stronger connection between CECED's training offerings and the actual needs of UNED’s academic staff. The article concludes with recommendations to strengthen future assessments and inspire similar practices in other educational contexts.
Keywords: Training; Training Needs Assessment; Design Thinking; Distance Learning; participatory methodologies